ANALISIS PERFORMA MOTOR LISTRIK BLDC 3000W PADA SEPEDA MOTOR KONVERSI HYBRID PLUG-IN - nurkalim (JEECAE (Journal of Electrical, Electronics, Control, and Automotive Engineering), 2025)
This study aims to comprehensively analyze the performance of a 3000 Watt Brushless DC (BLDC) electric motor implemented in a Jupiter MX 135 motorcycle converted into a Plug-in Hybrid Electric Vehicle (PHEV). The background of this study is based on the increasing need for environmentally friendly transportation solutions and the limited empirical data on the performance capabilities of electric motors in conversion applications. The research method used is quantitative experimental, with performance testing conducted in a laboratory using a BRT 50L dynamometer. The testing focused on pure electric drive mode (EV Mode) to measure key parameters such as torque, power, and speed. The results of five tests showed that the 3000W BLDC motor was capable of producing an average peak power of 6.38 kW (8.56 HP) and a peak torque of 48.99 Nm. The maximum speed recorded was 146.68 km/h, with sharp acceleration in the initial phase, which is a characteristic of the instant torque of electric motors. These findings confirm that the 3000W BLDC electric motor has very adequate performance and is suitable for application in PHEV motorcycle conversion systems, offering an alternative vehicle that is not only efficient but also high-performing. Keywords: Electric Motor, PHEV, 3000W BLDC, Dynotest, Conversion Motorcycle